Dynamic In-game Advertising in 3D Digital Games. A threat or a possibility - Raatikainen, Olli (NORDICOM, 2012)
Lately, digital games have developed concerning their use as a marketing medium. The present article is part of a study aimed at building a theoretical model for measuring and analyzing dynamic in-game advertising in 3D digital games. The study is explorative in nature, because it intends to build a new model of a real phenomenon based on one or more existing theories. Dynamic in-game advertising can be implemented in a 3D digital game without harming the gameplay experience, while still being effective from the marketer’s point of view. An optimized dynamic in-game advertisement is realistically and repeatedly, but subtly placed and interactive advertisement of a low-involvement product.
Keywords: in-game advertising; dynamic in-game advertising; gameplay experience; marketing communication; digital game; fi=Viestintätieteet|en=Communication Studies|